The impact of Gestational Weight Gain on Preeclampsia During COVID-19 Pandemic - Anugra, Lalu Rifal Hadi; Danianto, Ario; Irawati, Deasy (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective : To determine the Effect of Gestational Weight Gain on Preeclampsia During COVID-19 Pandemic in Public Health Centers of The West Lombok Regency Methods : This study is an observational analytic study that uses a case control study design (case control) starting by identifying patients with effects (preeclampsia and/or eclampsia) and groups without effects (no preeclampsia and/or eclampsia) and then retrospectively tracing their risk factors at 3 public health centers, which are located in West Lombok Regency, NTB Province, Indonesia namely Narmada, Kediri and Gunung Sari Health Centers. The analysis was carried out using the SPSS application. Results: Total of 120 samples were obtained, with 60 case samples and 60 control samples. During the COVID-19 pandemic with a time span of 2020-2021, subjects with weight gain that did not meet the recommendations had more preeclampsia, namely 56 people (93.3%) than subjects who did not had preeclampsia, which was 32 people (53.3 %). The value of Odds Ratio (OR) is 12,25 (95% Confidence Interval, 3.941-38.078). Conclusion : Based on this study, there was a significant relationship between the increase in BMI and the incidence of preeclampsia during the COVID-19 pandemic. The increase in BMI that is not in accordance with the recommendations is a risk factor for the occurrence of preeclampsia in pregnant women. The majority of preeclampsia occurs in 3rd trimester pregnant women. In addition, the Odds Ratio value obtained in this study increased by 6 times compared to similar studies conducted in non-pandemic conditions. Keywords : Preeclampsia, Eclampsia, Gestational Weight Gain, COVID-19